Aturan Bagi Hasil sebagai Faktor Penguat Kepercayaan (Trust) dalam Fintech Syariah: Kontribusi bagi Ekosistem Ekonomi Halal - Rendi Kurniawan; Sirajul Arifin; Luthfi Akmal Muzakki (Studia Economica : Jurnal Ekonomi Islam, 2026)
This study examines the role of profit-sharing regulations (Profit and Loss Sharing/PLS) in strengthening user trust (trust) within Islamic fintech and its contribution to the halal economy ecosystem. Using a qualitative descriptive approach through narrative literature review, this research analyzes regulatory documents, academic publications, official reports from OJK and DSN-MUI, and relevant secondary data. The findings indicate that profit-sharing mechanisms, which fundamentally differ from interest-based systems, foster transparency, fairness, and risk-sharing, thereby enhancing user trust. Unlike previous studies that predominantly focused on fintech adoption, technology aspects, or general market growth, this research highlights the central role of PLS regulations as a strategic factor in building trust, particularly in Sharia Securities Crowdfunding services. This study underscores the importance of standardizing contracts, strengthening regulations, improving accountability, and enhancing Sharia literacy to maintain trust and accelerate the development of the halal economy